Marx and virtual reality: the evolution of the area of anti-capitalist struggle - Mikhailouski, Vadzim S. (Journal of the Belarusian State University. Sociology, 2019)
The genesis, evolution and development trend of the Marxist values (classical Marxism, Leninism and neo-Marxism) were revealed. In axiological dimension, Marxism is a coherent process of developing the value of practice. Within the framework of the Marxist-Leninist tradition, an analytical attention was paid to the active violent action. Neo-Marxists suggested another interpretation of the value of practice which are the concepts of Cultural Revolution and self-organization and self-reproduction of masses. We suggest the potential of virtual reality as an area free from capitalism to become a new branch of Marxist thought. The threat is that capital can resolve class contradictions by declaring virtuality as the area of «consumer compensation». It is the IT elite, which being at the forefront of modern Marxism, can implement the concept of virtual overcoming of global alienation.
Keywords: anti-capitalist struggle; virtual reality; cultural revolution; marxism; multitude; neo-Marxism; alienation; consumption